Session 4: How can I rapidly upskill my large teacher workforce? - Koomar, Saalim; Proctor, Jamie (2022)
The Strategic Choices for Education Reform workshop held in Zimbabwe in November 2022 aimed to provide a forum for senior government officials to reflect and consider the strategic reform options for their countries. The objective was to convene officials in key positions in the ministries of education, higher education, finance, and planning to learn about important issues and approaches in education; exchange experiences and lessons; develop an understanding of what is necessary to reconstruct better and more resilient education systems; and to transform the large potential of young people, through human capital investments, into development and prosperity. EdTech Hub was invited to facilitate the day of the workshop focused on harnessing ICT for better teaching and learning. This presentation is one of several used in the workshop to promote learning, discussion, and problem solving among the participants. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Structured Pedagogy and EdTech - Adam, Taskeen; Chuang, Rachel; Haßler, Björn (EdTech Hub, 2021)
Keywords: _EdTechHub_Output; _MELA_seen; _coming soon; _cover:analysis:nopdf; dode_eth-src-eth; dode_eth-trf2-dode

Effective Teacher Education in Low-Connectivity Settings: A Curated Resource List - Koomar, Saalim; Allier-Gagneur, Zoé; McBurnie, Chris (EdTech Hub, 2020)
This list curates resources — both tools and initiatives — that can be adapted to support teacher education in low-connectivity settings, a prevailing challenge in Madagascar. Each example identifies the challenges; necessary prerequisites; pros and cons and; costs and impact assessment data where possible.
Keywords: C:Madagascar; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; W:Low connectivity and/or electricity; _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted; dode_eth-src-eth; dode_eth-trf2-dode

Characteristics of effective teacher education in low- and middle-income countries: What are they and what role can EdTech play? - Allier-Gagneur, Zoe; McBurnie, Chris; Chuang, Rachel; Haßler, Björn (EdTech Hub, 2020)
This paper analyses a range of literature reviews to identify characteristics of effective teacher education, including focusing on practical subject pedagogy; incorporating peer support and; creating a coherent policy environment.
Keywords: E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _forthcoming; _zenodoETH:submitted; _zenodoODE; docs.opendeved.net; dode_eth-src-eth; dode_eth-trf2-dode

Characteristics of effective teacher education in low- and middle-income countries: an annotated bibliography (HDR10C) - McBurnie, Chris; Allier-Gagneur, Zoe; Haßler, Björn (EdTech Hub, 2020)
Keywords: E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Using Education Technology to Support Students with Special Educational Needs and Disabilities in Low- and Middle-Income Countries - Coflan, Caitlin Moss; Kaye, Thomas (EdTech Hub, 2020)
This brief focuses on how policymakers can make decisions about EdTech to support learners with special educational needs and/or disabilities (SEND) while offering policymakers the rationale and tools to move towards an inclusive approach. It also includes a detailed annex with descriptions, costs, availability, and examples of accessible and assistive technologies.
Keywords: F: Helpdesk response; L:Special education needs and disabilities (SEND); LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-dode

15 EdTech research papers that we share all the time - Moss, Caitlin (EdTech Hub, 2020)
We hope you saw our recent blog post responding to questions we often get about interesting large-scale EdTech initiatives. Another question we are often asked is: “What EdTech research should I know about?”  As Sara’s blog post explains, one of the Hub’s core spheres of work is research, so we ourselves are very interested in […]
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

18 large-scale EdTech initiatives on our radar in 2020 - Moss, Caitlin (EdTech Hub, 2020)
During the EdTech Hub’s inception phase so far, one question we hear a lot is: “What interesting or notable EdTech initiatives are you seeing?” Another question usually follows: “Which ones are reaching scale?” This week we have joined the global education community in London for the Education World Forum and BETT meetings. This is a […]
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

Summarised Findings from the EdTech Hub Helpdesk - Chuang, Rachel; Moss Coflan, Caitlin (EdTech Hub, 2020)
As of December 2020, EdTech Hub’s Helpdesk has been active for nine months, responding to over 60 requests supporting decision-making on education technology. This document summarises our responses to six commonly asked questions across the topics of reaching marginalised learners, supporting teachers, and using EdTech to mitigate learning loss.
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:image; _r:CopiedFromEvLib; _zenodoETH; _zenodoETH:submitted

EdTech Initiatives Focused on Classrooms and Teachers: A Curated List for Rwanda - Chuang, Rachel; Koomar, Saalim (EdTech Hub, 2020)
This document was produced in response to a request from the FCDO Rwanda team for a curated list of EdTech initiatives related to the following focus areas: 1. Classroom software 2. Teacher education 3. School administration.
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted

Open Educational Resources in Africa: A Curated Resource List - Koomar, Saalim; Jull, Stephen (EdTech Hub, 2020)
This curated list defines Open Rducational Resources (OER), offers background on open-source licensing, and provides a review of OER that can be used in the sub-Saharan African context.
Keywords: C: Ghana; F: Helpdesk response; H: Open resources; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH

Open Education Resources in Africa: A Curated Resource List - Koomar, Saalim; Jull, Stephen (Zenodo, 2020)
This curated list defines open educational resources, offers background on open source licensing, and provides a review of OER relevant to the context of Ghana in response to an EdTech Hub helpdesk request. This document does not intend to set out a comprehensive list of OER used by teachers, students, parents or other stakeholders; rather, this document will identify exemplars of OER provided they are relevant to the Ghanaian context and focus on: reaching marginalised learners through offline or online content; reaching marginalised learners through mass media; using OER for teacher education; further useful resources and methods of implementing OER.